Characterizations of TIG welded joints of Unalloyed Commercially Pure Titanium Gr-2 for Weld Process Parameters (Fracture and Structural Integrity, 2019)
Titanium and Titanium Alloys can be welded by gas tungsten arc, gas metal arc, plasma arc and electron beam welding processes. Titanium material is a reactive metal and is sensitive to embrittlement by oxygen, nitrogen, and hydrogen gas, at elevated temperatures. Consequently, the metal must be protected from atmospheric contamination. This can be provided by shielding the metal with welding grade inert gas. The present work describes the application of TIG arc welding to titanium and  investigated the effect of welding parameters like weld current, weld gap and gas flow rate on mechanical properties of welded joints of unalloyed commercially pure titanium Gr-2 materials. Taguchi optimization method has been used to find out optimal setting of parameters for weld joints characterization. The welded joints showed an ultimate tensile strength of about 429 MPa with 23.33% elongation. A significant grain coarsening is noticed in the fusion zone consisting of α-phase in different direction bounded by β-phase. The hardness value at fusion zone and base metal are typically observed to be 235 and 145HV.
Keywords: TIG Welding; Titanium Gr-2; Process Parameters; Weld Characterization